A decade of research on Incontinence-Associated Dermatitis (IAD): Evidence, knowledge gaps and next steps. Issue 1 (February 2017) - Beeckman, Dimitri
Abstract: Background: Incontinence-Associated Dermatitis (IAD) is one of the clinical manifestations of Moisture- Associated Skin Damage (MASD). IAD is a common problem in aged patients with fecal and/or urinary incontinence. Aim: Update about IAD terminology, etiology, epidemiology, observation, prevention, and treatment. Methods: Integrative review. Results: The lack of an ICD-10 code and an internationally validated and standardized method for IAD data collection contribute to a variation in epidemiological data. Frequent episodes of incontinence (especially fecal), occlusive containment products, poor skin condition, reduced mobility, diminished cognitive awareness, inability to perform personal hygiene, pain, pyrexia, certain medications (antibiotics, immunosuppressants), poor nutritional status, and critical illness are associated with IAD. Correctly diagnosing IAD and distinguish it from pressure ulcers is difficult. Even though the clinical presentation of partial thickness pressure ulcers and IAD is similar, the underlying etiologic factors differ. However, incontinence and IAD were found to be risk factors for pressure ulcer development. IAD management should essentially focus on skin cleansing to remove dirt, debris and microorganisms; skin moisturization to repair or augment the skin's barrier; and the application of a skin barrier product to prevent skin breakdown by providing an impermeable or semi-permeable barrier on the skin. The body of evidence is still limited, but growing since the last decade. Conclusion: Incontinence causes disruptions of the skin barrier function and leads to superficial skin damage. Macerated skin and superficial skin changes due to incontinence are associated with pressure ulcer development. Skin maceration, chemical irritation, and physical irritation should be targeted to effectively prevent and treat IAD. Highlights: Incontinence causes skin barrier disruptions and leads to superficial skin damage. IAD is associated with pressure ulcer development. Skin maceration, chemical and physical irritation should be targeted to manage IAD. The body of evidence about IAD management is limited but growing the last decade. Tissue viability and incontinence experts must take the lead to develop this clinical area.